P664 SB5 and reference adalimumab show cross-immunogenicity in patients with inflammatory bowel disease or rheumatoid arthritis. (25th January 2019) - Gonçalves, J; Myung, G; Hong, E; Park, M; Jeong, D; Ghil, J
Abstract: Background: SB5 has been approved by the European Commission as a biosimilar of reference adalimumab. The study was aimed at analysing immunogenicity similarity including functional binding of TNFs between SB5 and its reference product in IBD and in RA. Further analysis was carried out to test cross-reactivity of anti-infliximab antibodies with SB5. Methods: Sera from IBD or RA patients treated with adalimumab with or without measurable antibodies-to-adalimumab (ATA) were tested for their cross-reactivity to SB5 or reference adalimumab. Functional inhibition of TNF binding was measured by graded concentrations of SB5 and reference adalimumab. Finally, sera with antibodies to infliximab (ATI) and ATA from IBD patients treated with reference infliximab and adalimumab were examined for cross-reactivity with SB5. Sera were tested by ELISA with the cut-off level of 2.3μg/ml-equivalent for antibody detection. Comparison of mean concentrations was tested by paired t -test (if normality was accepted) and Wilcoxon test (if normality was rejected), and a correlation was tested using Spearman correlation test. Results: There was no difference between the ATA concentration measured against SB5 or reference adalimumab lots in ATA+ IBD (30 sera) or RA sera (4 sera). Even though background signal generated in ATA- sera was higher in SB5 lot compared with two reference adalimumab lots ( P ≤ 0.001), the absolute difference was minimal to < 0.1 μg/ml (Figure 1a and b). Moreover, there was a strong correlation between titres of ATA to SB5 and reference adalimumab lots from reference adalimumab-sensitised IBD sera or SB5-sensitised RA sera (Figure 2a and b). Figure 2. (a) Correlation between ATA concentrations from reference adalimumab-sensitised IBD patients using the designated SB5 or reference adalimumab lots as the antigen for serum immune-reactivity. ATA, antibody-to-adalimumab; IBD, inflammatory- bowel disease; RA, rheumatoid arthritis. (b) Correlation between ATA concentrations from SB5-sensitised PA patients using the designated SB5 or reference adalimumab lots as the antigen for serum immune-reactivity. In addition, ATA from reference adalimumab-sensitised IBD patients had similar functional inhibition on TNF binding capacity between SB5 and reference adalimumab. Finally, ATI from reference infliximab-sensitised IBD sera did not cross-react with SB5. Conclusions: SB5 and reference adalimumab show cross-immunogenicity in that ATA similarly identify reference adalimumab and SB5 in IBD and RA patients. On the other hand, anti-infliximab antibodies do not cross-react with SB5, further supporting that SB5 and reference adalimumab share immunogenic profile but not with infliximab. Disclaimer: The study was conducted at Sheba Medical Center, Tel-Aviv, Israel